1998
DOI: 10.1073/pnas.95.11.6516
|View full text |Cite
|
Sign up to set email alerts
|

Does the colonic H,K-ATPase also act as an Na,K-ATPase?

Abstract: We previously have demonstrated that the colonic P-ATPase ␣ subunit cDNA encodes an H,K-ATPase when expressed in Xenopus laevis oocytes. Besides its high level of amino acid homology (75%) with the Na,K-ATPase, the colonic H,K-ATPase also shares a common pharmacological profile with Na,K-ATPase, because both are ouabain-sensitive and Sch 28080-insensitive. These features raise the possibility that an unrecognized property of the colonic H,K-ATPase would be Na ؉ translocation. To test this hypothesis, ionselect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 28 publications
(20 reference statements)
3
54
0
Order By: Relevance
“…As shown in Fig. 3, the presence of Na + /K + -ATPase a 1 subunit in the apical membranes can be excluded, allowing us to conclude that the previously measured Na + -and K + -stimulated ATPase activity found in the apical membranes of the colon is not due to Na + / K + -ATPase, but could be associated with some form(s) of the colonic H + /K + -ATPase, as suggested previously [27,28].…”
Section: Discussionsupporting
confidence: 52%
“…As shown in Fig. 3, the presence of Na + /K + -ATPase a 1 subunit in the apical membranes can be excluded, allowing us to conclude that the previously measured Na + -and K + -stimulated ATPase activity found in the apical membranes of the colon is not due to Na + / K + -ATPase, but could be associated with some form(s) of the colonic H + /K + -ATPase, as suggested previously [27,28].…”
Section: Discussionsupporting
confidence: 52%
“…This finding is significant, because Na ϩ /K ϩ ATPase activity is reduced in rat distal colon before tumor development (31). Furthermore, this activity has localization and pharmacological properties that match those reported for this H ϩ /K ϩ ATPase with Na ϩ /K ϩ activity (28,29,31). Notably, the Na ϩ /K ϩ ATPase ␣ and ␤ subunits suppress cell motility through activation of PI3 kinase and interaction with annexin II (32); thus decreased abundance could signal increasing cell motility.…”
Section: Discussionmentioning
confidence: 49%
“…Interestingly, we observed reduced non-gastric H ϩ /K ϩ ATPase ␣ in tumors. Although annotated as an H ϩ /K ϩ ATPase, the rat form resembles a Na ϩ /K ϩ ATPase (75% sequence identity) and possesses significant Na ϩ /K ϩ activity (28,29). The mouse variant also is similar to mouse Na ϩ /K ϩ ATPase (NP 659149; 65% sequence identity; Blast score: 1373; E-value Ͻ 10 Ϫ100 ) (30), suggesting it may transport sodium.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cougnon et al reported that HKc␣ cRNA could express both H-K and Na-K transport functions in Xenopus oocytes (15). As a result, it is not unlikely that our prior identification of Na,K-ATPase activity in apical membranes represented an expression of one or both H,K-ATPases and not basolateral membrane contamination.…”
mentioning
confidence: 85%